Visões deformadas de professores e futuros professores sobre a natureza da Ciência: uma revisão da bibliografia atual - Pecci, Matheus Guilherme (Universidade Federal de São Carlos, 2021)
Research on students and teachers’s conceptions of Science has been developed since the second half of the 20th century. Based on these researches, Norman G. Lederman initiated investigations into how the Nature of Science is manifested by teachers in the teaching-learning process. This movement in Science Teaching, which began to study the view of teachers, in particular, on the Nature of Science, motivated Gil-Peréz, Cachapuz, Fernandéz and other collaborators (2001, 2002, 2011) to formulate seven Deformed Visions of Science that group together inadequate conceptions about Science and scientific knowledge present in the minds of teachers. From these works, it was defined as the objective of this research to map the Deformed Visions of Science presented by Science teachers - and future Science teachers - in current researches in the area. Were obtained 54 works in the literature to compose the corpus of this research, of which 35 are articles, 3 are completion of course works, 13 are masters dissertations and 3 are doctoral theses. Using descriptors established prior to the research, it was obtained that the most frequent Deformed View of Science in the analyzed works, representing the one that most occurs among teachers, is the Empirical-Inductivist and Atheoretical view. It was also found that 41 of the 54 papers focused on data collection to obtain the Conceptions of Science of the researched teachers and future teachers, since the question "What is Science?" appears frequently in these surveys. Finally, from the theoretical references of the analyzed researches, it was found that the authors most used as reference were Gil-Peréz, Cachapuz and collaborators (2001).
Deformed views of teachers and future teachers on the nature of Science: a review of the current bibliography
Keywords: Visões deformadas da ciência; Natureza da ciência; Concepções de professores e futuros professores; Pesquisa de revisão bibliográfica; Deformed visions of science; Nature of science; Conceptions of teachers and future teachers; Literature review research; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM